Main non-odontogenic tumors found in child’s oral cavity: literature review - Silva, Alenildo Pereira da; Evangelista, Silvane e Silva (Revista Uningá, 2022)
Pediatricians and odontopediatricians commonly encounter numerous tumors in the oral cavity of infants and children, which may be presented as hamartomas and congenital malformations or even true neoplasms. Hence, this literature review aimed to describe the main non-cystic and non-odontogenic tumor alterations found in the oral cavity of children to help pediatric dentists diagnose and choose the appropriate treatment; this study was based on the scholarly content disclosure database. The articles found in this review were collected in the following databases: Scielo, PubMed, and Google Scholar. The search used the articles published on the theme based on the keywords referring to the subject. In the articles that were included in this study, we observed the degree of relevance to the academic environment, classical evidence, and recent articles published on the subject. It was possible to conclude that most tumors found in the oral cavity of children are benign, and surgical removal has been the primary means of treatment. Thus, it is important to emphasize the importance of a correct diagnosis to assess the type, size, and extent of these lesions and the risks caused during treatment before any procedure.